Immunomodulatory Approaches in Diabetes-Induced Cardiorenal Syndromes - Ammar, Lama A.; Nahlawi, Mohamad I.; Shayya, Nizar W.; Ghadieh, Hilda E.; Azar, Nadim S.; Harb, Frédéric; Eid, Assaad A. (Frontiers in Cardiovascular Medicine, 2021)
Immunomodulatory approaches are defined as all interventions that modulate and curb the immune response of the host rather than targeting the disease itself with the aim of disease prevention or treatment. A better understanding of the immune system continues to offer innovative drug targets and methods for immunomodulatory interventions. Cardiorenal syndrome is a clinical condition that defines disorders of the heart and kidneys, both of which communicate with one another through multiple pathways in an interdependent relationship. Cardiorenal syndrome denotes the confluence of heart-kidney relationship across numerous interfaces. As such, a dysfunctional heart or kidney has the capacity to initiate disease in the other organ via common haemodynamic, neurohormonal, immunological and/or biochemical feedback pathways. Understanding how immunomodulatory approaches are implemented in diabetes-induced cardiovascular and renal diseases is important for a promising regenerative medicine, which is the process of replacing cells, tissues or organs to establish normal function. In this article, we will be reviewing the epidemiology and classifications of cardiorenal syndrome. We will be emphasizing on the haemodynamic factors and nonhaemodynamic factors linking the heart and the kidneys. In addition, we will be elaborating on the immunomodulatory pathways involved in diabetes-induced cardiorenal syndrome namely, RAS, JAK/STAT and oxidative stress. Moreover, we will be addressing possible therapeutic approaches that target the former pathways in attempt to modulate the immune system.